Method for efficiently synthesizing basic nickel carbonate

Through the combination of the inverse addition process and competitive adsorbent, the problem of high impurity ion content in the existing alkaline nickel carbonate production is solved, and the preparation of high-purity products is realized, which improves process efficiency and reduces costs.

CN119660818AInactive Publication Date: 2025-03-21HUAIHUA J&C NEW MATERIALS RES & DEV LTD

Patent Information

Application Number
CN202510185810.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing production methods of alkaline nickel carbonate, the impurity ion content is high, making it difficult to produce high-purity products, and the process efficiency is low and the cost is high.

Method used

Using the inverse addition process, nickel salt is added to a mixed solution of sodium carbonate and sodium hydroxide, stirred at low temperature and high speed and added competitive adsorbent to adjust the pH value, then heat up and stir, magnets are separated and washed, and finally high-purity alkaline nickel carbonate is prepared by recrystallization.

Benefits of technology

The content of impurity ions in the product is significantly reduced, the purity of alkaline nickel carbonate is improved, the process efficiency is enhanced, and the production cost is reduced. The method is green and environmentally friendly, and the competitive adsorbent can be reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a method for efficiently synthesizing basic nickel carbonate, and belongs to the technical field of chemical preparation. Comprising the following steps: (1) preparing a mixed solution of sodium carbonate and sodium hydroxide; (2) under low-temperature and high-speed stirring conditions, dropwise adding a nickel salt solution into the mixed solution, adding a competitive adsorbent, adjusting the pH value of the solution, then heating, continuing stirring reaction, separating the competitive adsorbent by a magnet, centrifuging, washing and collecting prepared primary basic nickel carbonate; and (3) recrystallizing the primary basic nickel carbonate in an ethanol water solution, and drying to obtain the basic nickel carbonate. According to the preparation method disclosed by the invention, the content of impurity ions in the product is reduced, so that the high-purity basic nickel carbonate can be prepared, the synthesis efficiency is high, the production cost is relatively low, the method is green and environment-friendly, the competitive adsorbent can also be repeatedly utilized and recycled, the production cost is reduced, and the method has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical preparation, and in particular to a method for efficiently synthesizing basic nickel carbonate. Background Art

[0002] Basic nickel carbonate is an important inorganic fine chemical, mainly used to prepare various nickel salts. High-quality basic nickel carbonate can be used in the electronics industry. In addition, basic nickel carbonate is also widely used in electroplating, electroforming, enamel pigments and industrial catalyst industries.

[0003] There are currently three methods for producing basic nickel carbonate: adding the precipitant to the metal salt solution, collectively referred to as the "forward addition method"; adding the metal salt to the precipitant, collectively referred to as the "reverse addition method"; and adding the salt solution and the precipitant to the neutralization reactor at the same time in proportion, collectively referred to as the "parallel addition method". Different reaction processes have a great impact on the physical indicators Psd (particle size distribution), AD (apparent density), BET (specific surface area) of basic nickel carbonate, as well as the content of chemical indicators such as Na, S, Cl, etc. The difference in particle morphology also affects the difficulty of subsequent washing.

[0004] The method of preparing powder by liquid phase reaction to generate precipitation has the advantages of simple process and wide adaptability, and is a widely used process. However, in the current industrial production process, due to the influence of various factors such as raw material factors and process parameter control methods, the basic nickel carbonate product not only has a high impurity content, but also the impurities are not easy to remove during the washing process, which cannot meet the needs of some industries for high-purity basic nickel carbonate raw materials. Summary of the invention

[0005] The purpose of the present invention is to provide a method for efficiently synthesizing basic nickel carbonate, which reduces the content of impurity ions in the product, thereby being able to prepare high-purity basic nickel carbonate, and having high synthesis efficiency, low production cost, and being green and environmentally friendly. The competitive adsorbent can also be reused and recycled, thereby reducing the production cost and having broad application prospects.

[0006] The technical solution of the present invention is achieved in this way: The present invention provides a method for efficiently synthesizing basic nickel carbonate, comprising the following steps: (1) preparing a mixed solution of sodium carbonate and sodium hydroxide; (2) under low temperature and high-speed stirring conditions, adding a nickel salt solution dropwise to a mixed solution, adding a competitive adsorbent, adjusting the pH value of the solution, then heating and continuing to stir the reaction, separating the competitive adsorbent with a magnet, centrifuging, washing, and collecting the obtained primary basic nickel carbonate; the competitive adsorbent is prepared by depositing carbon nanotubes on the surface of intercalated montmorillonite and then depositing iron / zinc / zirconium oxides, and depositing magnetic ferrosoferric oxide, and connecting β-cyclodextrin to obtain a competitive adsorbent; (3) The primary basic nickel carbonate is recrystallized in an ethanol aqueous solution and dried to obtain basic nickel carbonate.

[0007] As a further improvement of the present invention, the molar ratio of the nickel salt, sodium carbonate and sodium hydroxide is 3:1-1.1:2, and the concentration of the sodium carbonate is 10-15wt%.

[0008] As a further improvement of the present invention, the nickel salt in step (2) is nickel sulfate or nickel chloride, the low temperature is 0-4°C, the speed of the high-speed stirring is 1000-1500r / min, the temperature is increased to 50-60°C, the amount of the competitive adsorbent added is 3-5wt%, the pH of the solution is adjusted to 8.2-8.5, and the solution used for washing is 0.5-1.5wt% ammonia solution.

[0009] As a further improvement of the present invention, the concentration of ethanol in the ethanol aqueous solution in step (3) is 40-60wt%.

[0010] As a further improvement of the present invention, the preparation method of the competitive adsorbent is as follows: S1. Preparation of intercalated montmorillonite: adding montmorillonite to water, adding anionic surfactant, stirring the reaction, centrifuging, washing, and drying to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: heating the intercalated montmorillonite to a first temperature under an inert gas, stopping the inert gas, introducing hydrogen, heating to a second temperature, introducing n-hexane, reacting at a constant temperature, and cooling to room temperature under an inert gas to obtain carbon nanotube-deposited montmorillonite; S3. Deposition of composite metal oxides: adding carbon nanotube-deposited montmorillonite and sodium carbonate to water to obtain a mixture, simultaneously adding dropwise alkali solution and a mixture of iron salt, zinc salt and zirconium salt, heating for crystallization, filtering, washing and drying to obtain composite metal oxide / carbon nanotube-deposited montmorillonite; S4. Deposition of magnetic ferroferric oxide: adding the composite metal oxide / carbon nanotube-deposited montmorillonite to water, adding ferric chloride and ferrous chloride, adding ammonia water dropwise, heating and stirring to react, filtering, washing, and drying to obtain magnetic particles; S5. Preparation of competitive adsorbent: Add magnetic particles and β-cyclodextrin into alkaline solution, heat and stir the reaction under the protection of inert gas, recover the magnet, wash and dry to obtain the competitive adsorbent.

[0011] As a further improvement of the present invention, the anionic surfactant in step S1 is at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, the mass ratio of montmorillonite to anionic surfactant is 10:1-2, and the stirring reaction time is 1-3h.

[0012] As a further improvement of the present invention, in step S2, the first temperature is 400-500°C, the ventilation rate of the hydrogen is 80-120mL / min, the second temperature is 600-700°C, the ventilation rate of the n-hexane is 0.1-0.3mL / min, and the constant temperature reaction time is 30-40min.

[0013] As a further improvement of the present invention, in step S3, the mass ratio of the carbon nanotube-deposited montmorillonite and the sodium carbonate is 4-7:3-5, the alkali solution is a 0.5-1 mol / L NaOH or KOH solution, the mass ratio of the iron salt, the zinc salt and the zirconium salt in the mixed solution containing the iron salt, the zinc salt and the zirconium salt is 7-10:2-4:3-5, the iron salt is ferric chloride, ferric nitrate or ferric sulfate, the zinc salt is zinc chloride, zinc nitrate or zinc sulfate, the zirconium salt is zirconium chloride, zirconium sulfate or zirconium nitrate, and the heating crystallization temperature is 60-70°C, and the time is 4-6h.

[0014] As a further improvement of the present invention, the mass ratio of the composite metal oxide / carbon nanotube deposited montmorillonite, ferric chloride and ferrous chloride in step S4 is 8-10:3.24:1.26, the pH value of the solution is adjusted to 9-10 by dripping ammonia water, the temperature of the heating and stirring reaction is 75-85°C, and the time is 5-7h.

[0015] As a further improvement of the present invention, in step S5, the mass ratio of the magnetic particles to β-cyclodextrin is 10:2-4, the alkali solution is 3-4 mol / L NaOH or KOH solution, the temperature of the heating and stirring reaction is 75-85°C, and the time is 1-3h.

[0016] The present invention has the following beneficial effects: Basic nickel carbonate has fast nucleation and slow growth, and generally has small particles and irregular morphology, so the impurity content is high, and it is difficult to obtain a high-purity product. The present invention adopts the "reverse addition method" to add metal salts to the precipitant. When just mixed, a low temperature of 0-4°C is used to suppress its nucleation speed, thereby reducing the adsorption of sodium ions, sulfate ions, chloride ions or nitrate ions by the generated tiny precipitate particles. At the same time, a competitive adsorbent is added, which can adsorb a large amount of impurity ions such as sodium ions, sulfate ions, chloride ions or nitrate ions, so as to avoid that the tiny particles are usually surrounded by the impurity ion adsorption layer. At the same time, the temperature is increased to promote the reaction, so that the tiny particles can grow quickly into basic nickel carbonate particles, reduce the adsorption of impurity ions in the process, grow in a suitable pH range, and undergo ammonia washing, recrystallization and other steps, so as to further reduce the content of impurity ions in the product, so as to obtain high-purity basic nickel carbonate, which can reach electronic grade, and has high synthesis efficiency, low production cost, and is green and environmentally friendly. The competitive adsorbent can also be reused and recycled, reducing the production cost.

[0017] The competitive adsorbent prepared by the present invention uses montmorillonite as a carrier, and has a large interlayer distance after intercalation, so that it is easy to realize the deposition of carbon nanotubes, composite metal oxides and magnetic ferroferric oxide. At the same time, a large number of hydroxide ions are contained between the layers, and electrostatic adsorption occurs with impurity ions. At the same time, the deposited carbon nanotube materials, composite metal oxides and magnetic ferroferric oxide have a large specific surface area, provide a large number of adsorption sites, and also contain abundant hydroxyl groups and the like, which can have electrostatic effects, π-π interactions (cyclodextrin, carbon nanotubes) or chemical bonding with impurity ions to enhance adsorption capacity, or improve the adsorption capacity of impurity ions and the like by forming surface defects (cyclodextrin, carbon nanotubes), thereby greatly promoting the competitive adsorption of impurity ions, effectively avoiding the accumulation of impurities in the production process of basic nickel carbonate, thereby having a great promoting effect on the preparation of high-purity basic nickel carbonate. At the same time, the competitive adsorbent can be separated by a magnet, is easy to achieve regeneration and reuse, and also reduces the production and use costs. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Preparation Example 1 Preparation of competitive adsorbent Here’s how: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was added to 200 mL of water, 1 g of sodium dodecylbenzene sulfonate was added, the reaction was stirred for 1 h, centrifuged, washed, and dried to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: 10 g of intercalated montmorillonite was evenly spread in the center of a quartz boat, heated to 400 ° C under nitrogen protection, stopped passing nitrogen, passed hydrogen at a flow rate of 80 mL / min, heated to 600 ° C, passed n-hexane at a flow rate of 0.1 mL / min, reacted at a constant temperature for 30 min, cooled to room temperature under nitrogen protection, and obtained carbon nanotube-deposited montmorillonite; S3. Deposition of composite metal oxides: 4 g of carbon nanotube-deposited montmorillonite and 3 g of sodium carbonate were added to 100 mL of water to obtain a mixture, and 50 mL of a 0.5 mol / L NaOH solution and 50 mL of a mixed solution containing 0.7 g of ferric chloride, 0.2 g of zinc chloride and 0.3 g of zirconium chloride were simultaneously added dropwise, heated to 60 ° C, crystallized for 4 h, filtered, washed, and dried to obtain composite metal oxide / carbon nanotube-deposited montmorillonite; S4. Deposition of magnetic ferroferric oxide: 8 g of composite metal oxide / carbon nanotube deposited montmorillonite was added to 200 mL of water, and under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, and ammonia was added dropwise to 9, heated to 75 ° C, stirred for 5 h, filtered, washed, and dried to obtain magnetic particles; S5. Preparation of competitive adsorbent: 10 g magnetic particles and 2 g β-cyclodextrin were added to 200 mL 3 mol / L NaOH solution, heated to 75°C under nitrogen protection, stirred for reaction for 1 h, and the magnet was recovered, washed, and dried to obtain a competitive adsorbent.

[0020] Preparation Example 2 Preparation of competitive adsorbent Here’s how: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was added to 200 mL of water, 2 g of sodium dodecyl sulfate was added, the reaction was stirred for 3 h, centrifuged, washed, and dried to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: 10 g of intercalated montmorillonite was evenly spread in the center of a quartz boat, heated to 500°C under nitrogen protection, stopped introducing nitrogen, introduced hydrogen at a flow rate of 120 mL / min, heated to 700°C, introduced n-hexane at a flow rate of 0.3 mL / min, reacted at a constant temperature for 40 min, and cooled to room temperature under nitrogen protection to obtain carbon nanotube-deposited montmorillonite; S3. Deposition of composite metal oxide: 7 g of carbon nanotube-deposited montmorillonite and 5 g of sodium carbonate were added to 100 mL of water to obtain a mixture, and 50 mL of a 1 mol / L KOH solution and 50 mL of a mixed solution containing 1 g of iron nitrate, 0.4 g of zinc nitrate and 0.5 g of zirconium nitrate were simultaneously added dropwise, heated to 70 ° C, crystallized for 6 h, filtered, washed, and dried to obtain a composite metal oxide / carbon nanotube-deposited montmorillonite; S4. Deposition of magnetic ferroferric oxide: 10 g of composite metal oxide / carbon nanotube deposited montmorillonite was added to 200 mL of water, and 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added under nitrogen protection, and ammonia was added dropwise for 10, heated to 85 ° C, stirred for 7 h, filtered, washed, and dried to obtain magnetic particles; S5. Preparation of competitive adsorbent: 10 g magnetic particles and 4 g β-cyclodextrin were added to 200 mL 4 mol / L KOH solution, heated to 85°C under nitrogen protection, stirred for reaction for 3 h, and the magnet was recovered, washed, and dried to obtain a competitive adsorbent.

[0021] Preparation Example 3 Preparation of competitive adsorbent Here’s how: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was added to 200 mL of water, 1.5 g of sodium dodecylbenzene sulfonate was added, the reaction was stirred for 2 h, centrifuged, washed, and dried to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: 10 g of intercalated montmorillonite was evenly spread in the center of a quartz porcelain boat, heated to 450°C under nitrogen protection, stopped introducing nitrogen, introduced hydrogen at a flow rate of 100 mL / min, heated to 650°C, introduced n-hexane at a flow rate of 0.2 mL / min, reacted at a constant temperature for 35 min, and cooled to room temperature under nitrogen protection to obtain carbon nanotube-deposited montmorillonite; S3. Deposition of composite metal oxide: 5.5 g of carbon nanotube-deposited montmorillonite and 4 g of sodium carbonate were added to 100 mL of water to obtain a mixture, and 50 mL of a 0.7 mol / L NaOH solution and 50 mL of a mixed solution containing 0.85 g of iron sulfate, 0.3 g of zinc sulfate and 0.4 g of zirconium sulfate were simultaneously added dropwise, heated to 65 ° C, crystallized for 5 h, filtered, washed, and dried to obtain a composite metal oxide / carbon nanotube-deposited montmorillonite; S4. Deposition of magnetic ferroferric oxide: 9 g of composite metal oxide / carbon nanotube deposited montmorillonite was added to 200 mL of water, and under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, and ammonia water was added dropwise to 9.5, heated to 80 ° C, stirred for 6 h, filtered, washed, and dried to obtain magnetic particles; S5. Preparation of competitive adsorbent: 10 g magnetic particles and 3 g β-cyclodextrin were added to 200 mL 3.5 mol / L KOH solution, heated to 80°C under nitrogen protection, stirred for reaction for 2 h, and the magnet was recovered, washed, and dried to obtain a competitive adsorbent.

[0022] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that step S2 is not performed.

[0023] The details are as follows: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was added to 200 mL of water, 1.5 g of sodium dodecylbenzene sulfonate was added, the reaction was stirred for 2 h, centrifuged, washed, and dried to obtain intercalated montmorillonite; S2. Deposition of composite metal oxides: 5.5 g of intercalated montmorillonite and 4 g of sodium carbonate were added to 100 mL of water to obtain a mixture, and 50 mL of a 0.7 mol / L NaOH solution and 50 mL of a mixed solution containing 0.85 g of iron sulfate, 0.3 g of zinc sulfate and 0.4 g of zirconium sulfate were simultaneously added dropwise, heated to 65 ° C, crystallized for 5 h, filtered, washed, and dried to obtain composite metal oxide precipitated montmorillonite; S3. Deposition of magnetic ferroferric oxide: 9 g of composite metal oxide precipitated montmorillonite was added to 200 mL of water, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added under nitrogen protection, 9.5 ammonia water was added dropwise, heated to 80 ° C, stirred for 6 h, filtered, washed, and dried to obtain magnetic particles; S4. Preparation of competitive adsorbent: 10 g magnetic particles and 3 g β-cyclodextrin were added to 200 mL 3.5 mol / L KOH solution, heated to 80°C under nitrogen protection, stirred for reaction for 2 h, and the magnet was recovered, washed, and dried to obtain a competitive adsorbent.

[0024] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that step S3 is not performed.

[0025] The details are as follows: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was added to 200 mL of water, 1.5 g of sodium dodecylbenzene sulfonate was added, the reaction was stirred for 2 h, centrifuged, washed, and dried to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: 10 g of intercalated montmorillonite was evenly spread in the center of a quartz porcelain boat, heated to 450°C under nitrogen protection, stopped introducing nitrogen, introduced hydrogen at a flow rate of 100 mL / min, heated to 650°C, introduced n-hexane at a flow rate of 0.2 mL / min, reacted at a constant temperature for 35 min, and cooled to room temperature under nitrogen protection to obtain carbon nanotube-deposited montmorillonite; S3. Deposition of magnetic ferroferric oxide: 9 g of carbon nanotube-deposited montmorillonite was added to 200 mL of water, and under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, and ammonia water was added dropwise to 9.5, heated to 80 ° C, stirred for 6 h, filtered, washed, and dried to obtain magnetic particles; S4. Preparation of competitive adsorbent: 10 g magnetic particles and 3 g β-cyclodextrin were added to 200 mL 3.5 mol / L KOH solution, heated to 80°C under nitrogen protection, stirred for reaction for 2 h, and the magnet was recovered, washed, and dried to obtain a competitive adsorbent.

[0026] Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that step S5 is not performed.

[0027] The details are as follows: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was added to 200 mL of water, 1.5 g of sodium dodecylbenzene sulfonate was added, the reaction was stirred for 2 h, centrifuged, washed, and dried to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: 10 g of intercalated montmorillonite was evenly spread in the center of a quartz porcelain boat, heated to 450°C under nitrogen protection, stopped introducing nitrogen, introduced hydrogen at a flow rate of 100 mL / min, heated to 650°C, introduced n-hexane at a flow rate of 0.2 mL / min, reacted at a constant temperature for 35 min, and cooled to room temperature under nitrogen protection to obtain carbon nanotube-deposited montmorillonite; S3. Deposition of composite metal oxide: 5.5 g of carbon nanotube-deposited montmorillonite and 4 g of sodium carbonate were added to 100 mL of water to obtain a mixture, and 50 mL of a 0.7 mol / L NaOH solution and 50 mL of a mixed solution containing 0.85 g of iron sulfate, 0.3 g of zinc sulfate and 0.4 g of zirconium sulfate were simultaneously added dropwise, heated to 65 ° C, crystallized for 5 h, filtered, washed, and dried to obtain a composite metal oxide / carbon nanotube-deposited montmorillonite; S4. Deposition of magnetic ferroferric oxide: 9 g of composite metal oxide / carbon nanotube precipitated montmorillonite was added to 200 mL of water. Under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added. Ammonia water was added dropwise to a concentration of 9.5. The mixture was heated to 80°C and stirred for 6 h. The mixture was filtered, washed and dried to obtain a competitive adsorbent.

[0028] Comparative Preparation Example 4 Compared with Preparation Example 3, the difference is that step S1 is not performed.

[0029] The details are as follows: S1. Preparation of intercalated montmorillonite: 10 g of montmorillonite was evenly spread in the center of a quartz porcelain boat, heated to 450°C under nitrogen protection, stopped introducing nitrogen, introduced hydrogen at a flow rate of 100 mL / min, heated to 650°C, introduced n-hexane at a flow rate of 0.2 mL / min, reacted at a constant temperature for 35 min, and cooled to room temperature under nitrogen protection to obtain carbon nanotube-deposited montmorillonite; S2. Deposition of composite metal oxides: 5.5 g of carbon nanotube-deposited montmorillonite and 4 g of sodium carbonate were added to 100 mL of water to obtain a mixture, and 50 mL of a 0.7 mol / L NaOH solution and 50 mL of a mixed solution containing 0.85 g of iron sulfate, 0.3 g of zinc sulfate and 0.4 g of zirconium sulfate were simultaneously added dropwise, heated to 65 ° C, crystallized for 5 h, filtered, washed, and dried to obtain a composite metal oxide / carbon nanotube-deposited montmorillonite; S3. Deposition of magnetic ferroferric oxide: 9 g of composite metal oxide / carbon nanotube deposited montmorillonite was added to 200 mL of water, and under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added, and ammonia water was added dropwise to 9.5, heated to 80 ° C, stirred for 6 h, filtered, washed, and dried to obtain magnetic particles; S4. Preparation of competitive adsorbent: 10 g magnetic particles and 3 g β-cyclodextrin were added to 200 mL 3.5 mol / L KOH solution, heated to 80°C under nitrogen protection, stirred for reaction for 2 h, and the magnet was recovered, washed, and dried to obtain a competitive adsorbent.

[0030] Example 1 This embodiment provides a method for efficiently synthesizing basic nickel carbonate, comprising the following steps: (1) Prepare 100 mL of a mixed solution containing 10 mmol sodium carbonate and 20 mmol sodium hydroxide; (2) At 0°C and 1000 r / min stirring, 100 mL of an aqueous solution containing 30 mmol of nickel chloride was added dropwise to 100 mL of the mixed solution, and the competitive adsorbent prepared in Preparation Example 1 was added in an amount of 3 wt %, and the pH of the solution was adjusted to 8.2. The mixture was then heated to 50°C and stirred for 30 min. The competitive adsorbent was separated by a magnet and centrifuged. The solid was washed with a 0.5 wt % ammonia solution, and the obtained primary basic nickel carbonate was collected. (3) The primary basic nickel carbonate is recrystallized in an ethanol aqueous solution (the concentration of ethanol is 40 wt%) and dried to obtain basic nickel carbonate.

[0031] Example 2 This embodiment provides a method for efficiently synthesizing basic nickel carbonate, comprising the following steps: (1) Prepare 100 mL of a mixed solution containing 11 mmol sodium carbonate and 20 mmol sodium hydroxide; (2) At 4°C and 1500 r / min stirring, 100 mL of an aqueous solution containing 30 mmol of nickel chloride was added dropwise to 100 mL of the mixed solution, and the competitive adsorbent prepared in Preparation Example 2 was added in an amount of 5 wt %, and the pH of the solution was adjusted to 8.5. The temperature was then raised to 60°C, and the stirring reaction was continued for 30 min. The competitive adsorbent was separated by a magnet, centrifuged, and the solid was washed with a 1.5 wt % ammonia solution to collect the obtained primary basic nickel carbonate; (3) The primary basic nickel carbonate is recrystallized in an ethanol aqueous solution (the concentration of ethanol is 60 wt%) and dried to obtain basic nickel carbonate.

[0032] Example 3 This embodiment provides a method for efficiently synthesizing basic nickel carbonate, comprising the following steps: (1) Prepare 100 mL of a mixed solution containing 10.5 mmol sodium carbonate and 20 mmol sodium hydroxide; (2) At 2°C and 1200 r / min stirring, 100 mL of an aqueous solution containing 30 mmol of nickel chloride was added dropwise to 100 mL of the mixed solution, and the competitive adsorbent prepared in Preparation Example 3 was added in an amount of 4 wt %, and the pH of the solution was adjusted to 8.3. The temperature was then raised to 55°C, and the stirring reaction was continued for 30 min. The competitive adsorbent was separated by a magnet, centrifuged, and the solid was washed with a 1 wt % ammonia solution to collect the obtained primary basic nickel carbonate; (3) The primary basic nickel carbonate is recrystallized in an ethanol aqueous solution (the concentration of ethanol is 50 wt%) and dried to obtain basic nickel carbonate.

[0033] Comparative Example 1 Compared with Example 3, the difference is that low-temperature mixing is not performed in step (2).

[0034] The details are as follows: (1) Prepare 100 mL of a mixed solution containing 10.5 mmol sodium carbonate and 20 mmol sodium hydroxide; (2) At room temperature and under stirring at 1200 r / min, 100 mL of an aqueous solution containing 30 mmol of nickel sulfate was added dropwise to 100 mL of the mixed solution, and the competitive adsorbent prepared in Preparation Example 3 was added in an amount of 4 wt %, and the pH of the solution was adjusted to 8.3. The temperature was then raised to 55° C. and the stirring reaction was continued for 30 min. The competitive adsorbent was separated by a magnet and centrifuged. The solid was washed with a 1 wt % ammonia solution and the obtained primary basic nickel carbonate was collected. (3) The primary basic nickel carbonate is recrystallized in an ethanol aqueous solution (the concentration of ethanol is 50 wt%) and dried to obtain basic nickel carbonate.

[0035] Comparative Example 2 Compared with Example 3, the difference is that the competitive adsorbent in step (2) is prepared by Comparative Preparation Example 1.

[0036] Comparative Example 3 Compared with Example 3, the difference is that the competitive adsorbent in step (2) is prepared by Comparative Preparation Example 2.

[0037] Comparative Example 4 Compared with Example 3, the difference is that the competitive adsorbent in step (2) is prepared by Comparative Preparation Example 3.

[0038] Comparative Example 5 Compared with Example 3, the difference is that the competitive adsorbent in step (2) is prepared by Comparative Preparation Example 4.

[0039] Comparative Example 6 Compared with Example 3, the difference is that no competitive adsorbent is added in step (2).

[0040] Comparative Example 7 Compared with Example 3, the difference is that step (3) is not performed.

[0041] The details are as follows: (1) Prepare 100 mL of a mixed solution containing 10.5 mmol sodium carbonate and 20 mmol sodium hydroxide; (2) At 2°C and 1200 r / min stirring, add 100 mL of an aqueous solution containing 30 mmol of nickel salt into 100 mL of the mixed solution, add the competitive adsorbent prepared in Preparation Example 3 in an amount of 4 wt%, adjust the solution pH to 8.3, then raise the temperature to 55°C, continue stirring the reaction for 30 min, separate the competitive adsorbent with a magnet, centrifuge, wash the solid with a 1 wt% ammonia solution, and collect the obtained basic nickel carbonate.

[0042] Test Example 1 The basic nickel carbonate prepared in Examples 1-3 or Comparative Examples 1-7 was tested for impurity ion content by combining atomic absorption spectroscopy with inductively coupled plasma atomic emission spectroscopy and ion selective electrode method.

[0043] The results are shown in Table 1.

[0044] Table 1

[0045] It can be seen from the above table that the impurity content in the basic nickel carbonate obtained in Examples 1-3 of the present invention is relatively low.

[0046] Test Example 2 The apparent density AD of the basic nickel carbonate obtained in Examples 1-3 or Comparative Examples 1-7 was tested according to GB / T 1479.1-2001.

[0047] The particle size D of the basic nickel carbonate obtained in Example 1-3 or Comparative Example 1-7 is measured according to GB / T 19077-2016. 50 .

[0048] The results are shown in Table 2.

[0049] Table 2

[0050] It can be seen from the above table that the apparent density of the basic nickel carbonate obtained in Examples 1-3 of the present invention is greater than 1, and the particle size is greater than 30 μm.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for efficiently synthesizing basic nickel carbonate, characterized in that: The following steps are involved: (1) preparing a mixed solution of sodium carbonate and sodium hydroxide; (2) under low temperature and high-speed stirring conditions, adding a nickel salt solution dropwise to a mixed solution, adding a competitive adsorbent, adjusting the pH value of the solution, then heating and continuing to stir the reaction, separating the competitive adsorbent with a magnet, centrifuging, washing, and collecting the obtained primary basic nickel carbonate; the competitive adsorbent is prepared by depositing carbon nanotubes on the surface of intercalated montmorillonite and then depositing iron / zinc / zirconium oxides, and depositing magnetic ferrosoferric oxide, and connecting β-cyclodextrin to obtain a competitive adsorbent; (3) The primary basic nickel carbonate is recrystallized in an ethanol aqueous solution and dried to obtain basic nickel carbonate.

2. The method according to claim 1, characterized in that The molar ratio of the nickel salt, sodium carbonate and sodium hydroxide is 3:1-1.1:2, and the concentration of the sodium carbonate is 10-15wt%.

3. The method according to claim 1, characterized in that In step (2), the nickel salt is nickel sulfate or nickel chloride, the low temperature is 0-4°C, the high speed stirring speed is 1000-1500r / min, the temperature is increased to 50-60°C, the amount of the competitive adsorbent added is 3-5wt%, the pH of the solution is adjusted to 8.2-8.5, and the solution used for washing is 0.5-1.5wt% ammonia solution.

4. The method according to claim 1, characterized in that: The concentration of ethanol in the ethanol aqueous solution in step (3) is 40-60wt%.

5. The method according to claim 1, characterized in that The preparation method of the competitive adsorbent is as follows: S1. Preparation of intercalated montmorillonite: adding montmorillonite to water, adding anionic surfactant, stirring the reaction, centrifuging, washing, and drying to obtain intercalated montmorillonite; S2. Preparation of carbon nanotube-deposited montmorillonite: heating the intercalated montmorillonite to a first temperature under an inert gas, stopping the inert gas, introducing hydrogen, heating to a second temperature, introducing n-hexane, reacting at a constant temperature, and cooling to room temperature under an inert gas to obtain carbon nanotube-deposited montmorillonite; S3. Deposition of composite metal oxides: adding carbon nanotube-deposited montmorillonite and sodium carbonate to water to obtain a mixture, simultaneously adding dropwise alkali solution and a mixture of iron salt, zinc salt and zirconium salt, heating for crystallization, filtering, washing and drying to obtain composite metal oxide / carbon nanotube-deposited montmorillonite; S4. Deposition of magnetic ferroferric oxide: adding the composite metal oxide / carbon nanotube-deposited montmorillonite to water, adding ferric chloride and ferrous chloride, adding ammonia water dropwise, heating and stirring to react, filtering, washing, and drying to obtain magnetic particles; S5. Preparation of competitive adsorbent: Add magnetic particles and β-cyclodextrin into alkaline solution, heat and stir the reaction under the protection of inert gas, recover the magnet, wash and dry to obtain the competitive adsorbent.

6. The method according to claim 5, characterized in that In step S1, the anionic surfactant is at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, the mass ratio of montmorillonite to anionic surfactant is 10:1-2, and the stirring reaction time is 1-3h.

7. The method according to claim 5, characterized in that In step S2, the first temperature is 400-500° C., the ventilation rate of the hydrogen is 80-120 mL / min, the second temperature is 600-700° C., the ventilation rate of the n-hexane is 0.1-0.3 mL / min, and the isothermal reaction time is 30-40 min.

8. The method according to claim 5, characterized in that In step S3, the mass ratio of the carbon nanotube-deposited montmorillonite and sodium carbonate is 4-7:3-5, the alkali solution is 0.5-1 mol / L NaOH or KOH solution, the mass ratio of the iron salt, zinc salt and zirconium salt in the mixed solution containing iron salt, zinc salt and zirconium salt is 7-10:2-4:3-5, the iron salt is ferric chloride, ferric nitrate or ferric sulfate, the zinc salt is zinc chloride, zinc nitrate or zinc sulfate, the zirconium salt is zirconium chloride, zirconium sulfate or zirconium nitrate, the heating crystallization temperature is 60-70°C, and the time is 4-6h.

9. The method according to claim 5, characterized in that The mass ratio of the composite metal oxide / carbon nanotube deposited montmorillonite, ferric chloride and ferrous chloride in step S4 is 8-10: 3.24:1.26, the pH value of the solution is adjusted to 9-10 by adding ammonia water, and the temperature of the heating and stirring reaction is 75-85°C and the time is 5-7h.

10. The method according to claim 5, characterized in that In step S5, the mass ratio of the magnetic particles to β-cyclodextrin is 10:2-4, the alkali solution is 3-4 mol / L NaOH or KOH solution, the temperature of the heating and stirring reaction is 75-85° C., and the time is 1-3 h.

Citation Information

Patent Citations

  • Preparation process of green environmentally-friendly high-adsorption-active adsorbent for printing and dyeing wastewater

    CN108176356A

  • Preparation method of carbon coated nickel nano-composite material

    CN109309214A

  • Preparation method of sodium-containing basic nickel carbonate

    CN110203977A

  • Graphene-supported ferroferric oxide magnetic powder particles and preparation method thereof

    CN110745813A

  • Nano zero-valent iron-copper-carbon microsphere material and preparation method thereof

    CN113546626A

Cited By

  • Pig urine resource utilization method and prepared organic fertilizer

    CN120923293A

  • Preparation method of basic nickel carbonate and mother liquor circulation desulfurization system

    CN121269827A

  • Basic nickel carbonate modified material and preparation method thereof

    CN121627072A

  • A basic nickel carbonate modified material and a preparation method thereof

    CN121627072B